The Impact of Zakat and Macroeconomics on Poverty in Indonesia: A Panel Data Analysis of 34 Provinces - Febrianto, M. Nanang; Herlina Wati; Zulfah Jannatul Karimah (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: Poverty is a multidimensional problem that requires integrated policies in its management as part of efforts to eradicate poverty. Objective: This study aims to examine the effects of zakat, gross domestic product, the open unemployment rate, and the Gini index on poverty across 34 provinces in Indonesia. Method: This study employed a quantitative, associative approach. The data are panel data from 34 provinces in Indonesia, covering 2019 to 2023, sourced from the Central Statistics Agency and the National Zakat Agency. Data analysis was conducted using a fixed-effects panel-data regression model.  Results: Zakat, Infaq, and Sedekah have a positive but insignificant effect on poverty. Gross Domestic Product has a negative but insignificant effect on poverty. Meanwhile, the Open Unemployment Rate and the Gini Index have positive and significant effects on poverty, indicating that increases in these variables are associated with higher poverty. Unemployment is driven by limited job opportunities, low skills, and limited experience, while the high Gini index (income inequality) stemming from unequal income distribution affects the cycle of poverty. Implication: The results can serve as a reference for developing plans and policies to optimize poverty alleviation, particularly in providing employment and inclusive income distribution.